Monocephalus Dibrachius Tetrapus Monster with Atresia ani in a Buffalo - Basera, Ashutosh; Agrawal, Jitendra Kumar; Sachan, Vikas; Kumar, Anuj; Saxena , Atul (The Indian Journal of Animal Reproduction, 2025)
A full term pregnant buffalo with a history of rupturing a water bag was presented in the clinic and both  forelimbs of the fetus were out of vagina. On gynaecological examination, the case was diagnosed as dystocia due to  a monster. Thereafter, with coordinated force and effort of 30 minutes, a monocephalic, dibrachius, tetrapus female  monster along with atresia ani condition in anterior longitudinal presentation with dorso-sacral position was  delivered. Animal recov-ered after follow-up treatment of 7 days.
Keywords: Buffalo; Dystocia; Fetus; Monster; Tetrapus